2011
DOI: 10.1007/s10803-011-1403-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Academic Achievement of Gifted Students with Autism Spectrum Disorder

Abstract: We are not well informed regarding the ability-achievement relationship for twice-exceptional individuals (very high cognitive ability and a diagnosed disability, e.g., autism spectrum disorder [ASD]). The research question for this investigation (N = 59) focused on the predictability of achievement among variables related to ability and education in a twice-exceptional sample of students (cognitive ability of 120 [91st percentile], or above, and diagnosed with ASD). We determined that WISC-IV Working Memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 22 publications
4
78
0
Order By: Relevance
“…Overall, several themes have emerged from cross-sectional regression-based prediction models of reading and mathematics abilities in high functioning subgroups, with findings suggesting a role for IQ, basic cognitive processes (e.g., processing speed and working memory), executive functions (e.g., attentional switching), and motor skills in explaining the variance in academic achievement in individuals with ASD (Assouline, Nicpon, & Dockery, 2012; May et al, 2013; Mayes & Calhoun, 2008). …”
Section: Predictors Of Achievement In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, several themes have emerged from cross-sectional regression-based prediction models of reading and mathematics abilities in high functioning subgroups, with findings suggesting a role for IQ, basic cognitive processes (e.g., processing speed and working memory), executive functions (e.g., attentional switching), and motor skills in explaining the variance in academic achievement in individuals with ASD (Assouline, Nicpon, & Dockery, 2012; May et al, 2013; Mayes & Calhoun, 2008). …”
Section: Predictors Of Achievement In Asdmentioning
confidence: 99%
“…In children with HFA, concurrent full scale IQ (FSIQ) was the single best predictor of reading, math, and writing achievement (Mayes & Calhoun, 2008). Furthermore, using a cross-sectional predictor model in a sample of cognitively gifted children with ASD (i.e., IQ > 120), Assouline et al (2012) found that working memory and processing speed accounted for significant variance (i.e., 61 percent) in reading achievement, working memory predicted written language achievement, and perceptual reasoning ability predicted oral language achievement. These findings suggest that basic domain general thinking skills (e.g., working memory and processing speed) also contribute to academic success in HFA.…”
Section: Predictors Of Achievement In Asdmentioning
confidence: 99%
“…However, poor comprehenders with ASD seldom process information quickly and do not adequately keep it active within their working memories (Assouline, Nicpon, & Dockery, 2012). Executive dysfunction theory (Ozonoff & Pennington, 1996) suggests that they also have cognitive difficulties in regard to flexibility, planning and self-monitoring.…”
Section: Surface-level Processingmentioning
confidence: 99%
“…Intellectual giftedness is common in moderate forms of ASDs, 78e80 where this cooccurrence has been conceptualized as one of "twice-exceptionalities". 80 These children with ASDs and intellectual giftedness exhibit both internalizing and externalizing e u r o p e a n j o u r n a l o f p a e d i a t r i c n e u r o l o g y 1 9 ( 2 0 1 5 ) 4 0 2 e4 1 0 behavioural problems. 80 As ASDs are thought to represent the high-level co-occurrence of continuously distributed quantitative traits, 81 it could be hypothesized that gifted children with a SVPD, emotional dysregulation, and a pathological cognitive disharmony, may be situated at the border of such developmental atypicalities entailing multiple impairments in high-order cognitive functioning.…”
mentioning
confidence: 99%
“…80 These children with ASDs and intellectual giftedness exhibit both internalizing and externalizing e u r o p e a n j o u r n a l o f p a e d i a t r i c n e u r o l o g y 1 9 ( 2 0 1 5 ) 4 0 2 e4 1 0 behavioural problems. 80 As ASDs are thought to represent the high-level co-occurrence of continuously distributed quantitative traits, 81 it could be hypothesized that gifted children with a SVPD, emotional dysregulation, and a pathological cognitive disharmony, may be situated at the border of such developmental atypicalities entailing multiple impairments in high-order cognitive functioning. 82 SVPD is also a feature of nonverbal learning disability (NVLD), or "Rourke's syndrome", which clinical manifestations includes neuropsychological impairment in the domains of arithmetic, spatial cognition, and nonverbal aspects of social cognition, together with a series of right-sided neurological soft-signs.…”
mentioning
confidence: 99%